Стилістика деталей міської архітектури Гуцульщини та Покуття третини ХХ століття - Радченко, А. (Інститут народознавства НАН України, 2007)
The article throws light upon some artistic peculiarities of profiled and carved details in urban architecture. Those consist of separate stylistic units. The ornament is determined by sophisticated complex of floral motives lent from different ssources.